Handling of Ventricular Fibrillation in the Emergency Setting - Szabó, Zoltán; Ujvárosy, Dóra; Ötvös, Tamás; Sebestyén, Veronika; Nánási, Péter P. (Frontiers in Pharmacology, 2020)
Ventricular fibrillation (VF) and sudden cardiac death (SCD) are predominantly caused by channelopathies and cardiomyopathies in youngsters and coronary heart disease in the elderly. Temporary factors e.g. electrolyte imbalance, drug interactions and substance abuses may play an additive role in arrhythmogenesis. Ectopic automaticity, triggered activity, and re-entry mechanisms are known as important electrophysiological substrates for VF determining the antiarrhythmic therapies at the same time. Emergency need for electrical cardioversion is supported by the fact that every minute without defibrillation decreases survival rates by approximately 7-10%. Thus, early defibrillation is an essential part of antiarrhythmic emergency management. Drug therapy has its relevance rather in the prevention of sudden cardiac death, where early recognition and treatment of the underlying disease has significant importance. Cardioprotective and antiarrhythmic effects of beta blockers in patients predisposed to sudden cardiac death were highlighted in numerous studies, hence nowadays these drugs are considered to be the cornerstones of the prevention and treatment of life-threatening ventricular arrhythmias. Nevertheless, other medical therapies have not been proven to be useful in the prevention of VF. Although amiodarone has shown positive results occasionally, this was not demonstrated to be consistent. Furthermore, the potential proarrhythmic effects of drugs may also limit their applicability. Based on these unfavourable observations we highlight the importance of arrhythmia prevention, where echocardiography, electrocardiography and laboratory testing play a significant role even in the emergency setting. In the following we provide a summary on the latest developments in cardiopulmonary resuscitation, and the evaluation and preventive treatment possibilities of patients with increased susceptibility to VF and SCD.